Towards Keynesian DSGD (isequilibrium) Modelling: Real-Financial Market Interactions with Heterogeneous Expectations Dynamics - Matthieu Charpe; Peter Flaschel; Florian Hartmann; Roberto Veneziani (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
We consider an alternative modelling approach to the mainstream DSGE paradigm, namely basically a Dynamic Stochastic General Disequilibrium model of continuous adjustment processes on interacting real and financial markets. We introduce heterogeneous capital gain expectations (chartists and fundamentalists) and show that the first type of agents tends to destabilise he economy. Global stability can be ensured if opinions favour fundamentalist behaviour far off the steady state. This interaction of expectations and population dynamics is bounding the real-financial market interactions, but allows for irregular behaviour within these bounds. Stability can be further improved by adding suitable policy measures.
urn:nbn:de:101:1-201211143571
Keywords: E12; E24; E31; E52; 330; Output dynamics; Portfolio Adjustments; Opinion Dynamics; Viability; Policy Measures; Dynamisches Gleichgewicht; Neukeynesianische Makroökonomik; Finanzmarkt; Erwartungstheorie; Anlageverhalten; Finanzanalyse; Tobinsteuer; Theorie